Assembly of Discrete Collagen–Chitosan Microenvironments into Multiphase Tissue Constructs. Issue 5 (26th November 2012) - Caldwell, David J.; Rao, Rameshwar R.; Stegemann, Jan P.
<x xml:space="preserve">Abstract</x> Modular assembly of protein–polysaccharide microenvironments into 3D macroscale tissue constructs is reported. Rapid and simple centrifugation and vacuum molding methods are used to create cohesive multiphase constructs with prescribed geometries. Human fibroblasts are shown to survive in the microenvironments and in the macroscale constructs. Control of the spatial organization in engineered tissues is a key to recreating the complex tissue architectures needed for regenerative therapies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>